EXPLORING SPEAKING ANXIETY : THE CAUSES Of ENGLISH LANGUAGE SPEAKING ANXIETY AT SMA N 2 BANGKINANG KOTA - Despita Yanti; Vitri Anggraini Hardi (Journal of English Language and Education, 2019)
Speaking is convinced as a skill that most frequently evokes anxiety among the students. Anxiety appears because of the lack of knowledge, the low desire to try to speak, fear of making mistakes and difficulty to understand on the teacher’s words. This research was aimed investigatly factors contributing to speaking anxiety at the third grade of SMA N 2 Bangkinang Kota. This is a Qualitative Research. The observation check list, the questionnaire, and the interview topic guide were used as the instruments to collect the data. The findings showed that fear of making mistakes is the biggest factor that make students anxiety in speaking English. Fear of making mistakescaused by some factors, there are : the students don’t understand because the lack of vocabulary, low structure, and don’t know how to pronounce the word. Then, the next factor is self-perception or self-esteem. This factor of language difficulties (lack of self-confidence, afraid about structure and speaking English correctly, they thought the other students more better in speaking English), concern about others perception, low self- confidence, lack of motivation and lack of communication and afraid of making mistakes. After that is social environment, they have limited exposure to target language and judgment from other people, and when they try to speak English their friends don’t understand and laugh them . And the last is a cultural difference. That is because different topic and different accent and they ere not used to using English to communicate in daily life.